Engineering applications of neural networks : 17th International Conference, EANN 2016, Aberdeen, Scotland, September 2-5, 2016. Proceedings /: 17th International Conference, EANN 2016, Aberdeen, Scotland, September 2-5, 2016. Proceedings. (2016) - Unknown
No abstract available